The Cultural Adaptation And Paralinguistic In McDonald’s Arabia Advertising: A Semiotic Analysis Using Roland Barthes’ Framework: English - Fathir Khalid; Dedi Supriadi; Siti Muslikah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study analyzes the verbal and nonverbal structures in McDonald's Arabic advertisement “ماك أربيا من ماكدونالدز” using Roland Barthes' semiotic approach. Through a descriptive analytical method with a qualitative approach, the researcher identifies paralinguistic elements to reveal McDonald's cultural adaptation strategies in the Arab market. The results of the study indicate that McDonald's implements a localization strategy through the use of standard Arabic combined with local dialects, cultural symbols such as traditional clothing, and Arab societal values. At the denotative level, the verbal structure includes local culinary terms and Arabic slogans, while the nonverbal structure depicts a happy family togetherness in an Arab environmental setting. At the connotative level, the advertisement aligns global modernity with local traditionalism, creating the perception that foreign products can integrate with Arab cultural identity without threatening local values. These findings contribute to the understanding of cross-cultural communication in global advertising and demonstrate how semiotics can reveal cultural adaptation strategies in contemporary advertising media.